The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
+20 votes
3.7k views

Consider the following experiment.

Step 1. Flip a fair coin twice.

Step 2. If the outcomes are (TAILS, HEADS) then output $Y$ and stop.

Step 3. If the outcomes are either (HEADS, HEADS) or (HEADS, TAILS), then output $N$ and stop.

Step 4. If the outcomes are (TAILS, TAILS), then go to Step 1.

The probability that the output of the experiment is $Y$ is (up to two decimal places)

asked in Probability by Loyal (7.1k points)
edited by | 3.7k views
+4
A much easier way for this would be:

Let $W = \text{We get a Y}$.
Let $D = \text{The game is decided after the first two tosses}$

The crucial observation here is that if we don't finish after the first two tosses, we are facing the same game again.

Therefore, $P(W/D^c) = P(W) \implies P(W/D) = P(W)$.

This gives us that $P(W) = P(W  \cap D)/P(D) = \frac{1/4}{1/4 + 2/4} = 0.33$

4 Answers

+31 votes
Best answer
Answer is ${0.33}$

$1^{st}$ time it is ${0.25}\left(\dfrac{1}{4}\right),$ when tail tail comes, entire process gets repeated, so next time probability of $Y$ to happen is ${0.25}\times {0.25}\left(\dfrac{1}{4}\times \dfrac{1}{4}\right),$ likewise it goes on as infinite GP

Sum of infinite GP $= \dfrac{a}{(1-r)}$

here, $a= \dfrac{1}{4}$ and $r =\dfrac {1}{4}$

so answer becomes $\dfrac{1}{3}$ i.e ${0.33}$
answered by Active (1.9k points)
edited by
0
@Sreyas, nice explanation,but can someone explain why the following solution isn't the answer..
p=prob((TAILS, HEADS))=1/4===getting Y
q=1-p(not getting Y)=3/4

so,all together....put it as....pq+p^2q+p^3q+...... +p^nq =1/4
0
Why the failure of getting something other than $Y$ in the second flip is not considered for computing the probability of getting Y in next flip.
+11
let $P$ be the probability that $Y$ is printed.

one-fourth of the time we have $Y$ is printed and $\dfrac{1}{4}^{th}$ of the time the experiment is repeated all again and we have the same chance for printing $Y$ again. which can be written as,

$P=\dfrac{1}{4}+\dfrac{1}{4} P$

$\dfrac{3}{4} P = \dfrac{1}{4}$

$P=\dfrac{1}{3} = .33$
+4

we can think like this also

 

+25 votes

Answer should be 0.33

$P(TH)=\dfrac{1}{4}$

$P(HH + HT)=\dfrac{1}{2}$

now if $TT$ comes then toss again,

So, $P(TTTH)=\dfrac{1}{16} $ and so on.... $P(TH+TTTH+\ldots) = \dfrac{1}{4} + \dfrac{1}{16}+\ldots= \dfrac{1}{3}$

answered by Junior (707 points)
edited by
+14 votes

P(getting the output Y) = P(TH) +P(TTTH) + P(TTTTTH) + P(TTTTTTTH) +  P(TTTTTTTTTH)+  P(TTTTTTTTTTTH)...........

 P(getting the output Y) = 1/4 + 1/42 +1/43 +1/44 +1/45 +1/46+................ = (1/4) / ( 1- 1/4) =1/3

The correct answer is 0.33 .
answered by Loyal (7.5k points)
0 votes

You can correct me if I am wrong.

answered by Junior (835 points)
Answer:

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
49,532 questions
54,123 answers
187,319 comments
71,044 users